Analisis Kelayakan Bisnis dan Strategi Pengembangan UMKM Kedai Kopi di Tengah Persaingan Industri Kreatif - Septi Putri Pratama (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The development of the coffee shop industry in Indonesia over the past five years has shown significant growth in line with changes in urban lifestyles and the growth of the creative economy. Coffee shops no longer function solely as places to consume beverages, but also as social spaces, alternative workplaces, and a medium for lifestyle expression. This study aims to analyze the business feasibility and formulate a development strategy for coffee shop MSMEs amidst the competitive creative industry, using the 247 Selatan Coffee Shop as a case study. The research method used a descriptive qualitative and quantitative approach through observation, interviews, consumer questionnaires, and literature review. The analysis covered aspects of consumer behavior, marketing, human resources, finance, technical and technological aspects, socio-cultural aspects, and legal aspects. The results indicate that the 247 Selatan Coffee Shop business is financially viable with a relatively short payback period, supported by strong market potential. A SWOT analysis indicates that appropriate development strategies include strengthening human resource quality, product innovation, and optimizing digital marketing. This research is expected to serve as an academic and practical reference for the development of coffee shop MSMEs in Indonesia